Relationship between Gender and Levels of Occupational Stress among Police Constables in Kisumu County, Kenya - Oweke, Joyce Atieno; Muola, James Matee; Ngumi, Owen (Journal Of Humanities And Social Scienc, 2014)
Stress is a major global health challenge affecting the well-being of service providers especially those working in the human service sectors like; police officers, teachers, health care providers and media specialists. This study was prompted by emerging information from studies that, stress is a silent killer that affects the health of service providers leading to; mental, physical, and emotional disorders. In Kenya and Kisumu County in particular studies on occupational stress among police constables are scanty The study adopted the Causal Comparative ex-post facto research design. The target population was 451 police constables and 12 Officers Commanding Stations in the four police divisions in Kisumu County. Stratified random sampling technique was used to sample 105 police constables and 4 Officers Commanding Station (OCS). The data was collected using a Police Constable Questionnaire and an Officer Commanding Station Interview Schedule. The instruments were validated by experts while reliability was estimated by use of Cronbach Alpha method for internal consistency. The questionnaire yielded a reliability coefficient of 0.88. Quantitative and qualitative data were obtained. Data was analyzed using Statistical Package for Social Sciences for Windows (Version 20). Descriptive statistics and inferential statistical (Chi-Square) were used in data analysis. The findings of the study that gender of the police constables influenced level of occupational stress. The study recommends that: Police service commission should develop a policy on stress management to guide the induction, operations and counselling of Police Constables on their day to day duties.
Keywords: Level of Occupational stress; Police Constables; Gender